Critique Against the Government: Freedom of Speech and Expression in Malaysia - Hamdan, Siti Nursyafiqah Binti; Nordin, Rohaida Binti (Journal of Indonesian Constitutional Law, 2025)
This research investigates the scope and constraints of free speech and expression in Malaysia, with a primary emphasis on critiques of the government. It aims to dissect how the liberties guaranteed by Article 10 of the Federal Constitution are limited by legislation such as the Sedition Act 1948, the Communications and Multimedia Act 1998, and the Printing Presses and Publications Act 1984. It contributes to the discourse on constitutional and human rights by highlighting how the selective enforcement of these statutes suppresses dissent, promotes self-censorship, and undermines democratic participation, while also offering comparative insights into how Malaysia’s legal framework diverges from international standards. The research employs a qualitative doctrinal method, analyzing constitutional provisions, statutory texts, case law, and international treaties. It is supplemented by secondary sources, including academic commentary and media reports, as well as a comparative analysis of other jurisdictions. The findings reveal that despite constitutional promises, freedom of expression remains heavily restricted through outdated and vaguely worded laws, illustrated by high-profile cases involving journalists, activists, and opposition figures that demonstrate patterns of legal intimidation and abuse of power; although digital media provides new avenues for discourse, it remains closely monitored by state authorities. The study concludes that legislative reform is essential to narrow the scope of restrictive laws, align domestic practices with international human rights norms, enhance judicial independence, and promote greater transparency and accountability, thereby ensuring a balanced approach that protects free expression while maintaining societal stability.